Elemental, isotopic and Ar40/39Ar data of the lake Carnegie Eucrite, old homestead 003 Howardite, and anomalous basaltic Achondrite Deakin 010 - Kennedy, T.; Jourdan, F.; Bevan, Alexander; Gee, M.; Downes, P.; Cliff, J.; Frew, A. (2012)
Introduction: Petrography, electron microprobe major and trace elements, oxygen isotope s and 40 Ar/ 39 Ar thermo-chronometry of a new cumulate eucrite (Lake Carnegie), a brecciated eucrite - like basaltic achondrite (Deakin 010), and a howardite (Old Homestead 003) from Western Australia are presented. Results and Discussion: Lake Carnegie is an equilibrated cumulate eucrite comprised of low-Ca pyroxene (Fs 29-61 , En 2 9-40 , Wo 5-42 ) and calcic plagioclase (An 91-9 7 , Ab 3-8 , Or 0-0.5 ) . Deakin 010 is a brecciated monomict eucrite and is comprised of low-Ca pyroxene (Fs 24-64 , En 27-36 , Wo 1-46 ) and calcic plagioclase (An 8 6-9 7 , Ab 3-11 , Or 0-3 ). Old Homestead 003 is a breccia of lithic clasts including eucrite fragments (some with sub - ophitic texture), and a minor diogenite component in a clastic, welded matrix of mineral fragments, and glass. Mineralogically, Old Homestead 003 includes rare olivine (Fa 4-4 6 , Fo 54-96 ,), Ca - pyroxene (Fs 9-6 8 , En 3-7 8 , Wo 1-86 ) and calcic plagioclase (An 88-9 7 , Ab 3-11 , Or 0.1-0. 8 ). Mineral compositions in Lake Carnegie and Deakin 010 indicate similar magmatic origins to other eucrites, and the Fe/Mn ratios of ferro-magnesian silicates in both eucrites and the howardite indicate an origin from the HED parent body [1], considered to be asteroid 4 Vesta [2,3]. For Lake Carnegie and Old Homestead 003, mineral-specific oxygen isotopic compositions support an origin on the HED parent body.However, in Deakin 010 oxygen is o topic compositions plot near the TFL and indicate an affinity with previously d e scribed anomalous basaltic achondrites, such as Bunburra Rockhole [4,5]. High-resolution 40 Ar/ 39 Ar thermochronometry dating of Lake Carnegie (4507 ± 20 Ma) suggests a mega impact at this time, Deakin 010 (3351 ± 65 Ma, ≥ 3.7 Ga, 3482 ± 36 Ma), and Old Homestead 003 (≥ 3.7 Ga) yielded only partially reset ages. Two other eucrites, Millbillillie (3722 ± 55 Ma, 3579 ± 28 Ma, 3313 ± 174 Ma) and Camel Donga (3693 ± 51 Ma) yielded an unprecedented number of well-defined plateau ages obtained on various mineral phases, and attributed to various impact events.